Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan - Tifani Nur Adinda; Muhamad Aziz Firdaus; Syahrum Agung (CV. ITTC INDONESIA, 2023)
This research aims to determine the influence of work motivation and work discipline on the performance of PT employees. Antam Tbk (UIBPEI) Pongkor. The research method used in this research is a quantitative method. The data collection technique in this research was carried out by distributing questionnaires to 46 PT employees. Antam Tbk (UIBPEI) Pongkor, which was then processed using the SmartPLS 4.0 application using the Structural Equation Modeling (SEM) analysis method. The results obtained from the influence of work motivation on employee performance with an original sample value of 0.389, T-statistics 3.442 > 1.96, and P-value 0.001 < 0.05, meaning that there is a positive and significant influence between work motivation and employee performance. The results obtained from the influence of work discipline on employee performance with an original sample value of 0.602, T-statistics 5.503 > 1.96, and Pvalue 0.000 < 0.05, meaning that there is a positive and significant influence between work discipline on employee performance. The results obtained from the influence of work motivation on work discipline with an original sample value of 0.841, T-statistics 6.757, and P-value 0.000 < 0.05, meaning that there is a positive and significant influence between work motivation and work discipline. The results obtained from the influence of work motivation through work discipline on employee performance with an original sample value of 0.506, T-statistics 4.194 > 1.96, and P-value 0.000 < 0.05, meaning that there is a positive and significant influence between work motivation through work discipline on employee performance.